Diversity and biogeography of a species‐rich ant fauna of the Australian seasonal tropics. (28th December 2016) - Andersen, Alan N.; Hoffmann, Benjamin D.; Oberprieler, Stefanie
Abstract: Although ants are an ecologically dominant and extensively studied faunal group throughout the tropics, there is a poor understanding of tropical ant diversity and distribution at large spatial scales. Here we use a collection developed from 3 decades of ant surveys to present the first analysis of ant diversity and biogeography of a large tropical region. Our objective was to document the species richness, composition, and biogeographic distributions of the ant fauna of the 400 000 km 2 "Top End" of Australia's Northern Territory. The known Top End ant fauna comprises 901 native species from 59 genera. The richest genera are Pheidole (90 species), Melophorus (83), Monomorium (83), Camponotus (71), Meranoplus (63), Polyrhachis (57), Rhytidoponera (50), Tetramorium (43), Cerapachys (32), and Iridomyrmex (31). The fauna is the center of diverse radiations within species‐groups of genera such as Meranoplus, Rhytidoponera, and Leptogenys . It also includes IndoMalayan species that have likely bypassed the normal dispersal route into Australia through Cape York Peninsula in North Queensland. Faunistic similarity with other regions of far northern Australia is associated more with rainfall than with geographic proximity. Most (60%) of Top End ant species have not been recorded elsewhere, and, despite uncertainties relating to species delimitation and sampling intensity, this appears to be a credible estimate of the level of endemism. Such exceptionally high endemism can be attributed to the Top End's geographic isolation from other regions of northern Australia with comparably high rainfall.